A chocolate box about Weimar: relationships between art and design in Barbara Bloom’s work (Palíndromo, 2024)
The American artist Barbara Bloom has been conducting research since the mid-1970s on a wide variety of artistic media, engaging in frequent interlocutions with the fields of photography, film, literature, music, advertising and design. In this paper, we aim to understand her approach to the universe of design based on the analysis of a specific piece of artwork entitled Weimar, past... future, and now? [A chocolate box about Weimar], 1995. In the light of the notion of "total design", developed by Hal Foster in the early 2000s, the analysis was conducted by comparing the strategies adopted by the artist with some of the principles of commercial design described in the guide "Universal Principles of Design", written by William Lidwell, Kristina Holden and Jill Butler. As a result, we highlight how Bloom's artwork assimilates and mimics the ways in which commercial design operates in order to subvert and redirect it, with the aim of awakening in the viewer a more distanced and questioning perception of their own daily reality.
Keywords: Barbara Bloom; art and design; art and tourism